Milieu Therapy as an Effort to Prevent Burnout Events in Nurses - Shindi Hapsari; Tri Ismu Pujiyanto; Eko Ristiarso; Aprin Rusmawati (Journal of Nursing Practice)
Background: Nurses have a high workload, so they are at risk of burnout. One of the non-pharmacological therapies that can overcome burnout is Milieu therapy.